THE ROLE OF BIODIVERSITY AND NATURAL DISASTERS IN THE HAITIAN CALAMITY - EXIME, ETHOL (Journal Internationale de Recherche et de Science sur la Résilience Environnementale, 2023)
This article aims to understand the role of Haitian biodiversity in the calamities faced by Haiti. With a population of 11 million over 27,750 km², the country is in a calamitous situation, with 60% of the population living in poverty and hunger. Haitian biodiversity, crucial for medicines and food, is affected by deforestation. The exploratory and qualitative research analyzes protected areas and their contributions. It concludes that biodiversity and natural disasters influence calamities, but calamities also affect biodiversity, emphasizing the complexity of the scenario. Limitations include the need for quantitative methods. More in-depth future studies on the subject are recommended.